Novel Impactor and Microsphere‐Based Assay Used to Measure Containment of Aerosols Generated in a Flow Cytometer Cell Sorter. Issue 2 (18th December 2018) - Perfetto, Stephen P.; Hogarth, Phillip J.; Monard, Simon; Fontes, Ben; Reifel, Kristen M.; Swan, Brandon K.; Baijer, Jan; Jellison, Evan R.; Lyon, Geoffrey; Lovelace, Patty; Nguyen, Richard; Ambrozak, David; et al.
Abstract: Today's state‐of‐the‐art cell sorting flow cytometers are equipped with aerosol containment systems designed to evacuate aerosols from the sort chamber during a sort. This biosafety device is especially important when the sort operator is sorting infectious or potentially infections samples. Hence, it is critical to evaluate the performance for this system in normal operation and in "failure" mode to determine the efficacy of containment. In the past decade, the most popular published method for evaluating containment has been the Glo‐Germ bead procedure. These highly fluorescent and multisize particles can easily be detected on a microscope slide and enumerated using a fluorescent microscope. Collecting particles on this slide is accomplished using an Aerotech impactor. This sampler collects potentially escaping aerosols from the sort chamber before enumerating any particles. Although the Glo‐Germ procedure has been adopted by many labs, there are several drawbacks with the procedure that have limited its adoption by cell sorter laboratories: The Aerotech impactor is a reusable device that requires rigorous cleaning between measurements. The surface area of the collection slide is large and difficult to scan on a fluorescence microscope. These beads produce a wide variation in sizes resulting in inconsistency in flow rates. Here, we describe a novel and replacement method utilizing a Cyclex‐d impactor and Dragon Green beads. This method was compared for sensitivity of detection of escaped aerosols with a published method for aerosol detection which utilizes a UV‐APS aerodynamic particle sizer and a UV‐excitable dye. One of the advantages of the Cyclex‐d system is the narrow‐defined field of collection as compared to the standard Glo‐Germ bead procedure, this means a smaller sampling area is used in the Cyclex‐d impactor as compared to the AeroTech impactor. In addition, the sensitivity of detection was found to be better using the Cyclex‐d collection device as compared to the standard Glo‐Germ bead procedure. © 2018 International Society for Advancement of Cytometry Abstract :